2007
DOI: 10.1200/jco.2007.25.18_suppl.4613
|View full text |Cite
|
Sign up to set email alerts
|

Phase II of trastuzumab and cisplatin in patients (pts) with advanced gastric cancer (AGC) with HER2/neu overexpression/amplification

Abstract: 4613 Background: Trastuzumab(T) exhibits activity in human gastric cancer cells that overexpress HER2/neu. We previously reported a 13.5% HER2/neu overexpression/amplification in AGC or gastroesofageal junction (GEJ) cancers (Grávalos C, et al. J Clin Oncol 24, 18S, 200s, abstr # 4089). We designed a phase II trial to determine the efficacy and tolerability of T and cisplatin(C) in pts with ACG with HER2/neu overexpression/amplification. Exploratory objectives include analysis of c-erbB-2 extracellular domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…16,[45][46][47] This phenomenon could represent a major drawback to sampling tumors for targeted cancer therapy. 2,5,45,46,48,49 In colon and lung cancer, intratumoral heterogeneity of KRAS mutation status is reported and crucial in selecting patients for anti-EGFR therapy. 50,51 It is described that testing DNA from a single sample of colorectal cancer will wrongly assign wild-type status to 10% patients, 50 suggesting multiple sampling in order to improve mutations detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,[45][46][47] This phenomenon could represent a major drawback to sampling tumors for targeted cancer therapy. 2,5,45,46,48,49 In colon and lung cancer, intratumoral heterogeneity of KRAS mutation status is reported and crucial in selecting patients for anti-EGFR therapy. 50,51 It is described that testing DNA from a single sample of colorectal cancer will wrongly assign wild-type status to 10% patients, 50 suggesting multiple sampling in order to improve mutations detection.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, treatment with human epidermal growth factor receptor 2 (HER2) inhibitor, Trastuzumab, has been demonstrated to increase overall survival in HER2-positive, inoperable locally advanced or metastatic gastric carcinoma. [3][4][5][6] ERBB2 is a key oncogene in many human cancers since its receptor tyrosine kinase activity triggers crucial intracellular signaling events for cell growth and survival. 7 In gastric cancer, ERBB2 positivity ranges from 7 to 27% of the tumors, [8][9][10][11][12][13] with high concordance rate between overexpression in immunohistochemistry and gene amplification tested by fluorescence in situ hybridization or chromogenic in situ hybridization.…”
mentioning
confidence: 99%
“…HER2 gene amplification or protein overexpression has been detected in 7-30% of primary gastric adenocarcinomas (2,4,(7)(8)(9). It has been reported that HER2 amplification and overexpression are influenced by the histological type and localisation of tumours (5)(6)(7)(8)(9)(10). Due to technological advances, HER2 can be easily identified; for example immunohistochemistry and fluorescence, chromogenic or silver in situ hybridisation have been used to detect HER2 protein overexpression and gene amplification (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The total response rate was only 35%. 24 No grade 4 toxicity related to trastuzumab was reported in any of these trials.…”
Section: Trastuzumab In Esophageal Cancer: the Clinical Aspectmentioning
confidence: 94%